2017
DOI: 10.1080/08941939.2017.1339151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy Analysis of Percutaneous Kyphoplasty Combined with Zoledronic Acid in the Treatment and Prevention of Osteoporotic Vertebral Compression Fractures

Abstract: Results of this study indicate that the clinical efficacy of PKP combined with aclasta in the treatment and prevention of OVCF is significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In research of spine fractures and non-spine fractures, the onset time of zoledronic acid is also shorter than that of alendronate. BPs increases callus thickness and improves VAS and disability scores (13,20,55,(59)(60)(61)(62). Hence, early application of BPs can effectively increase bone density, which can improve patientsq uality of life and functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In research of spine fractures and non-spine fractures, the onset time of zoledronic acid is also shorter than that of alendronate. BPs increases callus thickness and improves VAS and disability scores (13,20,55,(59)(60)(61)(62). Hence, early application of BPs can effectively increase bone density, which can improve patientsq uality of life and functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has shown that pamidronic acid has significant effect on bone mineral content and strength recovery in fractured rats (54). Early application of BPs has been shown to significantly reduce pain (55) which is conducive to early rehabilitation exercise and improves quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of ZOL treatment, such as flu-like symptoms, fever, and fatigue, have been widely reported [ 31 33 ], which generally lasts around 3–7 days. At the same time, the side effects of ZOL administration are generally tolerable and can be quickly relieved by self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the needle can be evaluated in the cross-section and sagittal and coronal planes, and determined accurately. The working channel is located in the pedicle, avoiding bone cement spillage due to bursting of the medial or lateral cortex of the pedicle [ 15 , 32 ]. Under DSA surveillance, when bone cement is injected during the operation, use of the two arms allows simultaneous observation of dispersion of cement in position [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%